PENGEMBANGAN MODEL PEMBELAJARAN LITERASI INTEGRATIF BERBASIS LOOSE PARTS (LILP) UNTUK MENINGKATKAN KEMAMPUAN MEMBACA ANAK USIA 5-6 TAHUN DI TK HARAPAN UMAT - Puspita Weni, Prilina Widya; Feri Faila Sufa; Yetty Isna Wahyuseptiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low reading ability of children aged 5-6 years at TK Harapan Umat, indicated by a classical learning approach and the demands of parents versus the non-drilling policy of Kurikulum Merdeka. This study aims to develop, test the feasibility, and evaluate the effectiveness of the Loose Parts-Based Integrative Literacy Learning Model (LILP) in improving early childhood reading skills. This study employed the Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were 35 children aged 5-6 years, selected using a saturated sampling technique. Data collection techniques included observation, interviews, documentation, and validation questionnaires. The results indicated that the LILP Model was categorized as highly feasible, with an average validation score of 87.6% from material experts, media experts, and early childhood practitioners. Furthermore, the implementation of the LILP model proved effective in significantly improving children's reading skills, increasing from an average score of 44.12% (Starting to Develop category) in the pre-implementation phase to 82.8% (Developing Very Well category) in the post-implementation phase. It can be concluded that the LILP model is feasible and effective to be applied as an alternative learning model to enhance early childhood literacy.